Clinical efficacy and safety of organ-sparing cystectomy: a systematic review and meta-analysis - Zhang,Yi; Peng,Lei; Zhang,Yang; Li,Hangxu; Li,Songbei; Zhang,Shaohua; Shi,Jianguo (PeerJ, 2024)
Background The clinical safety and efficacy of organ-sparing cystectomy (OSC) are subjects of ongoing debate, particularly concerning the potential increased risk of recurrence when retaining additional organs and its effectiveness in preserving sexual and urinary functions. Methods Adhering to the PRISMA 2020 statement and AMSTAR Guidelines, we conducted a systematic literature search up to February 2024 using PubMed, Embase, and Web of Science. The comparison focused on the clinical safety and effectiveness of OSC and standard radical cystectomy (SRC) in the treatment of bladder tumors. Our assessment covered several dimensions: Surgical safety outcomes (operation time, length of stay (LOS), estimated blood loss (EBL), and complications), oncological safety outcomes (recurrence rate, positive surgical margin rate, overall survival, and cancer-specific survival), and functional efficacy outcomes (daytime and nighttime urinary incontinence at 6 and 12 months, clean intermittent catheterization (CIC) rate, and erectile function within and after 1 year). Results The analysis included 19 eligible studies, encompassing 2,057 patients (1,189 OSC patients and 768 SRC patients). OSC demonstrated significant benefits in terms of erectile function and urinary continence without impacting CIC rates. No significant differences were observed in recurrence rate, positive surgical margin rate, overall survival, and cancer-specific survival. Furthermore, OSC and SRC were comparable in surgical safety outcomes, including operating time, LOS, EBL, and complications. Conclusions OSC offers notable advantages in erectile function and urinary continence. Despite limited clinical practice and potential selection bias, urologists may still consider OSC more based on their experience and specific patient factors.
Keywords: Radical cystectomy; Organ sparing; Nerve sparing; Urinary continence; Erectile function